ANALISIS MISKONSEPSI SISWA KELAS IV SEKOLAH DASAR PADA MATERI WUJUD ZAT DAN PERUBAHANNYA MENGGUNAKAN TES DIAGNOSTIK TWO-TIER - Maudy Aprilia; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the misconceptions of elementary school grade IV students on the material of substance forms and their changes and to examine the effectiveness of the use of two-tier diagnostic tests. This study uses a qualitative method with a Systematic Literature Review (SLR) approach to relevant scientific articles. Data were collected through literature studies and analyzed using qualitative descriptive techniques. The results of the study show that misconceptions are still found in many students, especially in understanding the nature of substances, distinguishing physical and chemical changes, and associating concepts with phenomena in daily life. The factors that cause misconception are students who are easier to understand real things than abstract concepts, learning methods that are not suitable, and the limitations of the evaluation instruments used. The use of two-tier diagnostic tests is considered more effective in identifying misconceptions because it can show the answers as well as the student's reasons. This study provides an overview of evaluation instruments that can be used to improve students' understanding of concepts.